(untitled) (Forseti. Law Review, 2025)
The integration of generative artificial intelligence in the practice of international arbitration has catalyzed a complex debate on its compatibility with the integrity of the arbitral process, specifically with the intuitu personae nature, regarding the possible scenarios of prohibited delegation of the arbitrator’s inherent functions to these digital tools, transgressing the principle of non-delegability of the arbitral function.